A Metal Reinforced Mandibular Implant Supported Overdenture Vs Conventional Maxillary Denture - A Case Report (Journal of Pharmaceutical Negative Results, 2023)
Background - Mandibular implant supported overdentures (IOD) overcome the difficulties faced by conventional mandibular dentures. Due to increased load and lesser thickness, they often fracture. In this case report, we present a metal reinforced mandibular IOD to overcome this drawback.Case description - An elderly, completely edentulous patient with a severely resorbed mandibular ridge reported to the department for a prosthesis. After a thorough study, it was decided to fabricate a mandibular IOD, reinforced with metal mesh to increase its strength.Discussion - Mandibular dentures are known to be prone to frequent fractures. In an attempt to increase its strength and longevity in function, we reinforce it with metal mesh. This case report is unique since, a metal reinforced mandibular implant supported overdentures are extremely rare.Conclusion - A regular follow-up of the patient revealed satisfactory patient outcome.